Evaluation of rammelsbergite (NiAs2) as a novel mineral for 187Re-187Os dating and implications for unconformity-related U deposits. (1st July 2020) - Chernonozhkin, Stepan M.; Mercadier, Julien; Reisberg, Laurie; Luais, Béatrice; Zimmermann, Catherine; Morlot, Christophe; Salsi, Lise; Lecomte, Andreï; Rouer, Olivier; Brouand, Marc; Doney, Amber; Ledru, Patrick
Abstract: Rammelsbergite (NiAs2 ) is often present in ore deposits worldwide in association with other arsenides, sulphides and sulfarsenides. This work demonstrates the value of the application of the Re-Os isotopic system to the dating of rammelsbergite. Using the example of the Cigar Lake uranium deposit (Athabasca Basin, Saskatchewan, Canada), our results show that rammelsbergite concentrates significant and variable amounts of Re when crystallizing, up to 1.6 µg g −1, while incorporating minimal common Os. Such characteristics make this mineral an ideal target for Re-Os isotopic dating, by both isochron and model age methods. Remarkable agreement of the Re-Os age of the rammelsbergite with the U-Pb age of the uranium oxide grains found inside one of the massive rammelsbergite veins confirms the applicability of the method. The selected rammelsbergite samples from the Cigar Lake uranium deposit yield a 187 Re- 187 Os isochron age of 1239 +33/−20 Ma. These results challenge a long-standing petrogenetic model which postulates contemporaneous U oxide and Ni-Co-arsenide deposition in unconformity-related uranium deposits. The new Re-Os age of rammelsbergite veins indicates that arsenide crystallization postdated the deposition of the primary uranium oxides at 1461–1341 Ma, implying that uranium oxides and nickel arsenides, as well as other sulphides and sulfarsenides, were not precipitated contemporaneously during a single hydrothermal event as previously proposed. The 187 Re- 187 Os data suggest that crystallization of rammelsbergite and co-genetic sulphides, arsenides and sulfarsenides was linked to the ca. 1270 Ma Mackenzie magmatic event, marked by the emplacement of mafic dikes throughout the Canadian Shield, including in the area of the Athabasca Basin. This study therefore suggests a new hypothesis for the origin of nickel, cobalt, sulfur and arsenic in unconformity-related U deposits of the Athabasca Basin. More broadly, the successful application of the 187 Re- 187 Os rammelsbergite chronometer in this geological context suggests that its application in other ore deposit environments worldwide is likely to provide similar insights. In this respect, the 187 Re- 187 Os chronometer applied to rammelsbergite, and potentially to other arsenides and sulfarsenides, represents a valuable complement to molybdenite dating because it can be used in systems that lack molybdenite.